Neutrophil lymphocyte ratio significantly improves the Framingham risk score in prediction of coronary heart disease mortality: Insights from the National Health and Nutrition Examination Survey-III - Shah, Neeraj; Parikh, Valay; Patel, Nileshkumar; Patel, Nilay; Badheka, Apurva; Deshmukh, Abhishek; Rathod, Ankit; Lafferty, James (International journal of cardiology, 2014)
Neutrophil lymphocyte ratio (NLR) has been shown to predict cardiovascular events in several studies. We sought to study if NLR predicts coronary heart disease (CHD) in a healthy US cohort and if it reclassifies the traditional Framingham risk score (FRS) model. We performed post hoc analysis of National Health and Nutrition Examination Survey-III (1998–94) including subjects aged 30–79years free from CHD or CHD equivalent at baseline. Primary endpoint was death from ischemic heart disease. NLR was divided into four categories: <1.5, ≥1.5 to <3.0, 3.0–4.5 and >4.5. Statistical analyses involved multivariate Cox proportional hazards models as well as discrimination, calibration and reclassification. We included 7363 subjects with a mean follow up of 14.1years. There were 231 (3.1%) CHD deaths, more in those with NLR>4.5 (11%) compared to NLR<1.5 (2.4%), p<0.001. Adjusted hazard ratio of NLR>4.5 was 2.68 (95% CI 1.07–6.72, p=0.035). There was no significant improvement in C-index (0.8709 to 0.8713) or area under curve (0.8520 to 0.8531) with addition of NLR to FRS model. Model with NLR was well calibrated with Hosmer–Lemeshow chi-square of 8.57 (p=0.38). Overall net reclassification index (NRI) was 6.6% (p=0.003) with intermediate NRI of 10.1% (p<0.001) and net upward reclassification of 5.6%. Absolute integrated discrimination index (IDI) was 0.003 (p=0.039) with relative IDI of 4.3%. NLR can independently predict CHD mortality in an asymptomatic general population cohort. It reclassifies intermediate risk category of FRS, with significant upward reclassification. NLR should be considered as an inflammatory biomarker of CHD.